TYPES AND APPLICATION OF QUALITATIVE RESEARCH METHODS IN ISLAMIC RELIGIOUS EDUCATION (PAI) RESEARCH - Siti Rahmah; Norlaila; Dina Hermina (As-Sulthan Journal of Education, 2025)
This study discusses the types and application of qualitative research methods in Islamic Religious Education (PAI) research. The scope of the study includes four types of qualitative research: case studies, grounded theory, phenomenology, and ethnography. The purpose of the study is to explain these types and their application in the context of Islamic Religious Education. The research method used is library research with data collection techniques in the form of literacy and content analysis. The results of the study show that the four methods have different characteristics and applications in Islamic Religious Education. Case studies are suitable for understanding specific phenomena, grounded theory for developing new theories, phenomenology for revealing the meaning of experience, and ethnography for understanding culture in the context of Islamic Religious Education. In conclusion, qualitative research methods are very relevant in Islamic Religious Education research to explore deep meanings and contexts related to religious values ​​and educational practices.